2012
DOI: 10.4049/jimmunol.1201415
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Intrinsic Abrogation of TGF-β Signaling Delays but Does Not Prevent Dysfunction of Self/Tumor-Specific CD8 T Cells in a Murine Model of Autochthonous Prostate Cancer

Abstract: Adoptive T cell therapy (ACT) for the treatment of established cancers is actively being pursued in clinical trials. However, poor in vivo persistence and maintenance of anti-tumor activity of transferred T cells remain major problems. Transforming growth factor beta (TGFβ) is a potent immunosuppressive cytokine that is often expressed at high levels within the tumor microenvironment, potentially limiting T cell mediated anti-tumor activity. Here, we used a model of autochthonous murine prostate cancer to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 79 publications
(95 reference statements)
2
23
0
Order By: Relevance
“…In contrast to the profound antitumor effect of adoptive cell transfer and TGF-b blockade in this study, Chou et al (36) have recently observed that adoptively transferred T cells derived from OT-I TGFbRII knockout mice display only limited antitumor effects and are rendered tolerant in a mouse model of autochthonous prostate cancer. One clear difference between these studies is that in our study a cancer-driving Ag was the target of adoptively transferred T cells, whereas Chou et al (36) targeted an Ag that did not play a role in tumor development or the maintenance of the malignant phenotype.…”
Section: Discussionmentioning
confidence: 44%
See 4 more Smart Citations
“…In contrast to the profound antitumor effect of adoptive cell transfer and TGF-b blockade in this study, Chou et al (36) have recently observed that adoptively transferred T cells derived from OT-I TGFbRII knockout mice display only limited antitumor effects and are rendered tolerant in a mouse model of autochthonous prostate cancer. One clear difference between these studies is that in our study a cancer-driving Ag was the target of adoptively transferred T cells, whereas Chou et al (36) targeted an Ag that did not play a role in tumor development or the maintenance of the malignant phenotype.…”
Section: Discussionmentioning
confidence: 44%
“…One clear difference between these studies is that in our study a cancer-driving Ag was the target of adoptively transferred T cells, whereas Chou et al (36) targeted an Ag that did not play a role in tumor development or the maintenance of the malignant phenotype. Therefore, the likelihood of the emergence of tumor Ag loss variants would have been greater in the study by Chou et al (36), but whether tumor Ag loss variants occurred in their study was not directly addressed.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations